Acute exacerbation of idiopathic pulmonary fibrosis model in the rats using bleomycin and lipopolysaccharides - Kurniawan, Sandy Vitria; Louisa, Melva; Zaini, Jamal; Surini, Silvia; Soetikno, Vivian; Wuyung, Puspita Eka; Uli, Rosemary Ceria Tatap (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study was conducted to establish a rat model of acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF) using the combination of bleomycin (BLM) and lipopolysaccharides (LPS). Materials and Method: Twenty-four male Sprague Dawley rats were allocated into two equal groups: the sham or the bleomycin and lipopolysaccharides-induced AE-IPF group (BLM-LPS). On Day 7, BLM intratracheally and LPS intraperitoneally were both used to administer AE-IPF. The BLM-LPS group and its respective sham group were terminated on Days 8, 14, or 21. Samples of bronchoalveolar lavage fluid (BALF) and lungs were taken and investigated for cell count and histopathology. Results: On Day 8, histological analysis revealed inflammatory cell infiltration with edema and hyaline membrane, and the BALF differential cell count revealed high neutrophil counts. By having a higher collagen density area and Ashcroft modified score than the sham group on Day 14, the BLM-LPS group displayed significantly lower oxygen saturation, alveolar air area, and a fibrotic appearance. However, there was a spontaneous resolution in inflammation and fibrotic appearance on Day 21 after the BLM administration. Conclusions: By combining BLM and LPS, it was possible to create a successful rat model of AE-IPF. The present model showed the peak exacerbation on Day 8 and the fibrotic peak on Day 14, which gradually improved. The optimal time for the new AE-IPF therapeutic intervention was determined to be between Days 8 and 14. J. Adv. Vet. Anim. Res., 10(2): 196–204, June 2023 http://doi.org/10.5455/javar.2023.j669